1995
DOI: 10.1103/physreva.52.1125
|View full text |Cite
|
Sign up to set email alerts
|

L-subshell ionization of heavy elements by carbon and nitrogen ions of energy 0.4–1.8 MeV/amu

Abstract: L-shell x-ray production and subshell ionization cross sections have been measured for 0.4 -1.8-MeV/amu carbon and nitrogen ions for selected heavy elements with 72 & Z~~90. The results yre compared with the predictions of the ECPSSR theory [perturbed-stationary-state (PSS) theory with energyloss (E), Coulomb deflection (C), and relativistic (R) corrections] describing both direct ionization and electron-capture processes and the semiclassical approximation (SCA} calculations for direct ionization.For both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
1
19
2
Order By: Relevance
“…Originally, the number of additional vacancies in higher subshells was deduced from the measured x-ray en- [18,19]. In the energy range that overlaps with our present work for C → Pt and Au, following Berinde et al [20], Semaniak et al [15] derived the probabilities for ionization of M and N subshells from changes in relative L x-ray peak yields once protons were replaced with carbon ions. While, with Larkins scaling [21] to deduce the number of multiple vacancies from energy shifts and relative intensities redistribution, this approach evolved into a standard procedure [22], Pajek et al [23] demonstrated that changes in both position and width of x-ray peaks are the most reliable determinants of the outer-shell ionization probabilities.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 92%
See 3 more Smart Citations
“…Originally, the number of additional vacancies in higher subshells was deduced from the measured x-ray en- [18,19]. In the energy range that overlaps with our present work for C → Pt and Au, following Berinde et al [20], Semaniak et al [15] derived the probabilities for ionization of M and N subshells from changes in relative L x-ray peak yields once protons were replaced with carbon ions. While, with Larkins scaling [21] to deduce the number of multiple vacancies from energy shifts and relative intensities redistribution, this approach evolved into a standard procedure [22], Pajek et al [23] demonstrated that changes in both position and width of x-ray peaks are the most reliable determinants of the outer-shell ionization probabilities.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 92%
“…The L-subshell ionization cross sections for 4.8-21.6-MeV carbon on Pt and Au by Semaniak et al [15] were already corrected for effects of multiple ionization; unfortunately, the measured x-ray production cross sections were not given in Ref. [15]. Table IV lists other cross sections found in the literature for gold, after correction for multiple ionization with Eqs.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 96%
See 2 more Smart Citations
“…Doǧan et al [21] have measured L l , L α , L β and L γ X-ray fluorescence cross-sections using two different energies 59.5 and 123.6 keV. In some studies, targets were excited with X-ray tube [22][23][24][25][26], protons [27][28][29][30], electrons [31][32][33] and ions [34][35][36][37] as an alternative to radioisotopes.…”
Section: Introductionmentioning
confidence: 99%